PENGARUH CURRENT RATIO (CR), QUICK RATIO (QR), DEBT TO ASSETS RATIO (DAR), DAN DEBT TO EQUITY RATIO (DER) TERHADAP PROFITABILITAS PADA SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Melati, Rima; Mursalin, Mursalin; Ilhamsyah, Ilhamsyah (Jurnal Manajemen dan Profesional, 2024)
This study aims to examine the effect of Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio on Profitability in the banking sub-sector listed on the Indonesia Stock Exchange. The population in this study are all financial statements of banking sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The samples used were 10 companies. The analysis technique used in this study is the classical assumption test which consists of a normality test, multicollinearity test, autocorrelation test, heteroscedasticity test and multiple regression analysis, correlation coefficient, coefficient of determination (R2) and hypothesis testing which consists of a t-test (partial) and f-test (simultaneous). The results of this study conclude that partially only the Quick Ratio has no effect on Return on Assets, while the Current Ratio, Debt to Assets Ratio and Debt to Equity Ratio have an effect on Return on Assets. Simultaneously Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio together have a significant effect on Return on Assets.